Pharmacological and molecular analysis of the effects of Huangqi Jianzhong decoction on proliferation and apoptosis in GES-1 cells infected with H. pylori - Jingnan Hu; Jingnan Hu; Tao He; Jianfang Liu; Jianfang Liu; Sujie Jia; Bolin Li; Weichao Xu; Man Liao; Man Liao; Lifang Guo (Frontiers Media S.A., 2022)
Background: Infection with Helicobacter pylori (H. pylori) can cause chronic gastritis and other digestive tract diseases, and represents a public health concern. Current anti-H. pylori treatment can result in antibiotic resistance and other adverse reactions. Huangqi Jianzhong decoction (HQJZD) is a prescription form of traditional Chinese medicine for chronic gastritis that increases probiotics and inhibits H. pylori. In this study, its anti-bacterial activity against H. pylori receives a preliminary evaluation, and a pharmacology analysis is performed to predict its underlying mechanisms.Methods: Human GES-1 cells are divided into a blank control group, a model group, a HQJZD low-dose (2.08 mg·mL−1), a high-dose group (4.16 mg·mL−1), and a positive control group (amoxicillin, 5 μg·mL−1). After culture, the CCK-8 method is used to detect cell viability; flow cytometry is used to detect cell apoptosis rate; and RT-qPCR is used to detect the expression of mRNA virulence factors, including HpPrtC, OPiA, IceA1, and BabA2. Network pharmacology analysis and molecular docking were performed to explore the mechanisms of HQJZD in treating H. pylori gastritis, based on its anti-H. pylori infection effect.Results: We noted lower cell survival rates in the model group, but higher apoptosis rates and mRNA expressions of HpPrtC, OPiA, IceA1, and BabA2 than in the control group (p < 0.05). Compared to the model group, the cell survival rate of each dosage group of Huangqi Jianzhong decoction and the positive control group increased significantly, while the apoptosis rate and the mRNA expressions of HpPrtC, OPiA, IceA1, and BabA2 were decreased significantly. The effect in each HQJZD group was dose-dependent (p < 0.05). Network pharmacological analysis involving 159 signaling pathways was used to screen 6 key active components of HQJZD and 102 potential target proteins for the treatment of H. pylori-related gastritis. The molecular docking results revealed that the 6 active compounds had a strong binding ability with the target proteins of ALB, IL-6, AKT1, IL-1B, and JUN.Conclusion: HQJZD effectively increases the proliferation rate of human GES-1 cells after infection, while reducing the level of apoptosis. The mechanism may be related to multiple components, multiple targets and pathways, which provides a scientific basis for further elucidating the mechanism of action, the pharmacodynamic material basis, and the clinical application of HQJZD against H. pylori infection.